A blended control strategy for intercepting high-speed target in high altitude. (September 2018) - Zhang, Youan; Wu, Huali; Liu, Jingmao; Sun, Yumei
To intercept target with high speed in high altitude, a blended control strategy is presented. The control strategy consists of two controls, one is the aerodynamic rudder control which is always switched on, another is the lateral jets control which is switched on only when the state variables' prediction at impact point suggests that the only aerodynamic rudder control is not enough to achieve interception. The objective of this strategy is to save consumption of lateral jets, which is necessary in the case of limited number of jets. The algorithm of state variables' prediction at impact point is summarized through recursive calculation using the analytic solutions of state variables of the kinematics with consideration of the dynamics of the interceptor (missile) by piecewise linearization and smart approximation. Considering the uncertain dynamics of the interceptor with blended control, a head pursuit robust guidance law is designed based on time-scale separation and robust control, where, the nonlinear deviation dynamics of the relation that the lead angle of the interceptor changes in proportion with that of the target, and the uncertain acceleration dynamics, are treated as the slow subsystem, while the uncertain pitch angular rate dynamics is treated as the fast subsystem. Numerical simulations are performed to verify the performance of the proposed guidance law.